Characterization of a novel thogotovirus isolated from Amblyomma testudinarium ticks in Ehime, Japan: A significant phylogenetic relationship to Bourbon virus - Ejiri, Hiroko; Lim, Chang-Kweng; Isawa, Haruhiko; Fujita, Ryosuke; Murota, Katsunori; Sato, Tomomi; Kobayashi, Daisuke; Kan, Miki; Hattori, Masashi; Kimura, Toshiya; Yamaguchi, Yukie; Takayama-Ito, Mutsuyo; et al. (Virus research, 2018)
•A new thogotovirus was isolated from Amblyomma testudinarium ticks in Japan.•Oz virus (OZV) was genetically and biologically characterized.•OZV is closely related to Bourbon virus, a human-pathogenic thogotovirus in the US. The genus Thogotovirus, as represented by Thogoto virus and Dhori virus, comprises a group of arthropod-borne viruses, most members of which are transmitted by ticks. Here we report the genetic and biological characterization of a new thogotovirus, designated Oz virus (OZV), isolated from the hard tick Amblyomma testudinarium in Ehime, Japan. OZV efficiently replicated and induced a cytopathic effect in Vero cells, from which enveloped pleomorphic virus particles were formed by budding. OZV could also replicate in BHK-21 and DH82 cells and caused high mortality in suckling mice after intracerebral inoculation. Phylogenetic analyses of six viral proteins indicated that OZV is clustered with Dhori and related viruses, and is most closely related in glycoprotein (GP) and matrix protein (M) sequences to Bourbon virus, a human-pathogenic thogotovirus discovered recently in the United States. Our findings emphasize the need for understanding the geographic distribution and ecology of OZV and related viruses and for reevaluation of the medical and public health importance of thogotoviruses.